Establishment of Oulenziella gen. nov. for Oulenzia bakeri (Hughes, 1962) (Acari: Winterschmidtiidae) - Fan, Qing-Hai; George, Sherly; Li, Dong-Mei; Zhang, Zhi-Qiang (Zootaxa, 2015)
A new genus, Oulenziella, is proposed for Oulenzia bakeri (Hughes, 1962), a species originally collected on jute (Corchorus sp., Malvaceae) from India. Oulenziella bakeri (Hughes, 1962) comb. nov. is re-described. Oulenzia gossypii Meyer & Rodrigues, 1965 collected from Gossypium sp. in Mozambique is considered a junior synonym of Oulenziella bakeri. The new genus differs from Oulenzia in having hT present on tibiae I and II, kT on tibia IV, la and ra on tarsus II, w and r on tarsus III, e and f on tarsi I–III; and by seta d on tarsi III and IV positioned at level of apical 1/8 to 1/6 of the segments.